Human PD-1hiCD8+ T Cells Are a Cellular Source of IL-21 in Rheumatoid Arthritis - Higashioka, Kazuhiko; Yoshimura, Motoki; Sakuragi, Takahide; Ayano, Masahiro; Kimoto, Yasutaka; Mitoma, Hiroki; Ono, Nobuyuki; Arinobu, Yojiro; Kikukawa, Makoto; Yamada, Hisakata; Horiuchi, Takahiko; Akashi, Koichi; et al. (Frontiers in Immunology, 2021)
Background: Rheumatoid arthritis (RA) is a prototypical autoantibody-driven autoimmune disease in which T-B interactions play a critical role. Recent comprehensive analysis suggests that PD-1+CD8+ T cells as well as two distinct IL-21-producing PD-1+CD4+ T cell subsets, follicular helper T (Tfh) and peripheral helper T (Tph) cells, are involved in the pathogenesis of RA. Herein, we aimed to clarify a generation mechanism of IL-21-producing CD8+ T cells in humans, and to characterize this novel subset in patients with RA. Methods: CD8+ T cells in the peripheral blood (PB) and synovial fluid (SF) of healthy control (HC) and patients with RA were subject to the analysis of IL-21 mRNA and protein. We evaluated the surface marker, cytokine and transcription profiles of IL-21-producing CD8+ T cells in HCPB, RAPB and RASF. Results: IL-21-producing CD8+ T cells were enriched in the CD45RA-(memory) PD-1+, especially PD-1hi subpopulation, and IL-12 and IL-21 synergistically induced IL-21 production by naïve CD8+ T cells. Memory PD-1hiCD8+ T cells in HCPB facilitated plasmablast differentiation and IgG production in an IL-21-dependent manner. In addition, PD-1hiCD8+ T cells in RASF and RAPB produced large amounts of IL-21 and were characterized by high levels of CD28, ICOS, CD69, HLA-DR, and CCR2 but not CXCR5. Furthermore, PD-1hiCD8+ T cells expressed high levels of transcripts of MAF and PRDM1, a feature observed in Tph cells. Conclusions: Identification of IL-21-producing PD-1hiCD8+ T cells expands our knowledge of T cell subsets with B helper functions in RA. Selective targeting of these subsets could pave an avenue for the development of novel treatment strategies for this disease.